Cloning in Indian Advertisements: Getting Two for the Price of One? - Banerji, Amit; Khan, Mohd Iqbal; Wani, Mudasir Ahad (Indian Journal of Marketing, 2013)
Due to the presence of various niches in a large segment and to cater to the maximum possible audience within it, the concept of the multiple roles played by the same person in Indian cinema is being used with greater frequency in Indian advertisements. Clones serve the purpose of controlling advertisement costs and at the same time, target the segment and niches within it effectively.